Peningkatan Nilai Ekonomis Sampah Dengan Metode Takakura, Desa Ngunut, Kecamatan Babadan, Kabupaten Ponorogo - Setyaningsih, Erlyka; Widyaningrum, Premi Wahyu; Chamidah, Siti (Khadimul Ummah, 2019)
Human life daily inseparable with litter. Various activities can create waste, all activities at, households the office, the restaurant, the market, tourist attractions etc. Garbage distinguished into the organic and inorganic. Both of these types of this garbage has the potential to pollute the environment. The waste problem may arise in urban areas or rural. Therefore need to find a solution waste management comprehensively, integrated, economical, efficient, and safe for the environment, and able to change the community. Method takakura first introduced in 2004 in the city surabaya by the japanese named Koji Takakura. The program aims to bring skills to the community in managing and processing waste with simple.This activity also as a receptacle for gave them knowledge and insight of management manner of manage process trash. It is also as a forum to discuss of methods of takakura. and applied by the community. The final result of this activity is to raise public awareness to manage and process waste and increasing economic value, garbage in the village Ngunut.